Relative comparison of chronic kidney disease-mineral and bone disorder rat models - Zhang, Xiaoqiong; Li, Ting; Wang, Lijuan; Li, Yanhui; Ruan, Taoren; Guo, Xiaohong; Wang, Qin; Meng, Xianli (Frontiers in Physiology, 2023)
Objective: The aim of this study is to establish a suitable animal model of chronic kidney disease–mineral and bone disorder (CKD–MBD) by comparing CKD–MBD rat models induced by 5/6 Nx, AN, and UUO, accompanied by a low-calcium and high-phosphorus diet. Methods: Sprague‒Dawley rats were randomly divided into four groups: control group, 5/6 nephrectomy (5/6 Nx) group, Adriamycin nephropathy (AN) group, and unilateral ureteral obstruction (UUO) group. Serum biochemical indices were measured to evaluate renal function, mineral and bone metabolism, the severity of CKD–MBD, and the status of bone transformation. Hematoxylin–eosin staining (HE) and Masson’s trichrome (Masson) staining were used for histopathological analysis of the kidney. Goldner’s trichrome (Goldner) and tartrate-resistant acid phosphatase (TRAP) staining were utilized to observe bone mineralization and osteoclasts in the femur, respectively. Micro-CT images were applied to study the structure of the femur. The expression levels of osterix and cathepsin K in the femur were measured by immunohistochemistry (IHC) to confirm the status of bone transformation. Results: The levels of serum creatinine (Scr) and blood urea nitrogen (BUN) in the 5/6 Nx and AN group rats were significantly higher than those in the control rats, and this change was accompanied by marked changes in the levels of calcium (Ca), phosphate (Pi), intact parathyroid hormone (i-PTH), fibroblast growth factor 23 (FGF23), osteocalcin (OC), and cross-linked C-telopeptide of type 1 collagen (CTX-1); UUO group rats exhibited slight and inconsistent variations in the levels of Scr, BUN, Ca, Pi, i-PTH, FGF23, OC, and CTX-1 in serum. Histopathological analysis of the kidney showed that the UUO group rats suffered serious fibrosis and 5/6 Nx group rats exhibited severe focal calcification. Histopathological analysis of the femur showed that the AN group rats had minimal bone mineralization and that the 5/6 Nx group rats had overactive osteoclasts. Micro-CT revealed that the AN model had the most severe bone destruction and that the 5/6 Nx model had the least severe bone loss among the three models. The expression of cathepsin K in the femur was significantly increased in all models, while the expression of osterix in the femur was only significantly increased in the 5/6 Nx model. Conclusion: 5/6 Nx, AN, and UUO accompanied by a low-calcium and high-phosphorus diet successfully induced CKD–MBD in rats. The 5/6 NX model presented the progression of high-turnover bone disease, with consistency between biochemical indices in serum and histomorphometric analysis of the femur, and the AN and UUO models developed a severe deterioration in bone quantity and severe bone resorption; however, the changes in biochemical indices were subtle in the UUO model, and liver injury was obvious in the AN model.